Identification of Immune Related LRR-Containing Genes in Maize (Zea mays L.) by Genome-Wide Sequence Analysis - Wei Song; Baoqiang Wang; Xinghua Li; Jianfen Wei; Ling Chen; Dongmin Zhang; Wenying Zhang; Ronggai Li (International Journal of Genomics)
A large number of immune receptors consist of nucleotide binding site-leucine rich repeat (NBS-LRR) proteins and leucine rich repeat-receptor-like kinases (LRR-RLK) that play a crucial role in plant disease resistance. Although many NBS-LRR genes have been previously identified in Zea mays, there are no reports on identifying NBS-LRR genes encoded in the N-terminal Toll/interleukin-1 receptor (TIR) motif and identifying genome-wide LRR-RLK genes. In the present study, 151 NBS-LRR genes and 226 LRR-RLK genes were identified after performing bioinformatics analysis of the entire maize genome. Of these identified genes, 64 NBS-LRR genes and four TIR-NBS-LRR genes were identified for the first time. The NBS-LRR genes are unevenly distributed on each chromosome with gene clusters located at the distal end of each chromosome, while LRR-RLK genes have a random chromosomal distribution with more paired genes. Additionally, six LRR-RLK/RLPs including FLS2, PSY1R, PSKR1, BIR1, SERK3, and Cf5 were characterized in Zea mays for the first time. Their predicted amino acid sequences have similar protein structures with their respective homologues in other plants, indicating that these maize LRR-RLK/RLPs have the same functions as their homologues act as immune receptors. The identified gene sequences would assist in the study of their functions in maize.